2012
DOI: 10.1097/ico.0b013e31823e2ac6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Boston Keratoprosthesis Implantation for Failed Keratoplasty After Keratolimbal Allograft

Abstract: Despite successful KLAL outcomes and systemic immunosuppression, patients who undergo ocular surface reconstruction with KLAL are still at risk for subsequent keratoplasty failure. Keratoprosthesis is a viable salvage therapy for visual rehabilitation in these patients. Adequate immunosuppression is important in postoperative management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Artificial corneas undoubtedly can improve vision but should be considered in cases when PKP has failed or expected to fail (e.g., in the setting of extensive stromal vascularization) [121126]. Currently, the Boston keratoprosthesis remains the main option in patients in which it has not been possible to restore corneal clarity and a normal ocular surface with any of previous measures [121, 127].…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial corneas undoubtedly can improve vision but should be considered in cases when PKP has failed or expected to fail (e.g., in the setting of extensive stromal vascularization) [121126]. Currently, the Boston keratoprosthesis remains the main option in patients in which it has not been possible to restore corneal clarity and a normal ocular surface with any of previous measures [121, 127].…”
Section: Surgical Managementmentioning
confidence: 99%
“…Currently, the Boston keratoprosthesis remains the main option in patients in which it has not been possible to restore corneal clarity and a normal ocular surface with any of previous measures [121, 127]. Their long-term risks, the need for life-long regular followups, and adherence to daily antibiotic prophylaxis are some of the issues that may make some patients less than ideal candidates for keratoprosthesis [122, 124, 125].…”
Section: Surgical Managementmentioning
confidence: 99%
“…159164 Currently, the Boston Type 1 keratoprosthesis ( B1-KPro ) is the most widely used device for restoring vision in patients who have failed previous corneal procedures. 159,165 Placement of a keratoprosthesis with or without a shunt may be considered 6 months after inflammation subsides (Figure 11). 106,166 The B1-KPro study group found excellent anatomical retention in patients with ocular chemical injuries: 94% after 1 year and 89% after 2 years.…”
Section: Management Of Chronic Phasementioning
confidence: 99%
“…For unilateral disease, conjunctival limbal autograft may be the best option. For bilateral disease, allogeneic tissues are needed as stem cell sources [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%